Impact of the K-line in patients with ossification of the posterior longitudinal ligament: Analysis of sagittal cervical curvature changes and surgical outcomes - Tang, Zhongxin; Chen, Tailong; Tan, Jun; Zhang, Huafeng (Frontiers in Surgery, 2023)
Objective This study aimed to investigate the relationship of the K-line with sagittal cervical curvature changes and surgical outcomes in patients with cervical ossification of the posterior longitudinal ligament (OPLL). Methods We retrospectively reviewed 84 patients with OPLL who underwent posterior cervical single-door laminoplasty. The patients were divided into a K-line-positive (+) group and a K-line-negative (−) group. Perioperative data, radiographic parameters, and clinical outcomes were compared between the two groups. Results Of 84 total patients, 50 patients were in the K (+) group and 29 patients were in the K (–) group. Neurological function improved in both groups after laminoplasty. The C2–7 Cobb angle, T1 slope, and C2–7 sagittal vertical axis were significantly changed in the K(−) group compared with those in the K (+) group before the operation and at the 3-month and final follow-ups. Conclusion Neurological function was recovered in both groups, and the clinical effect on the K (+) group was better than that on the K (−) group. The cervical curvature in patients with OPLL tends to be anteverted and kyphotic after laminoplasty and is an important factor in reducing the clinical effect.